Neuropsychological deficits in myotonic muscular dystrophy. - Malloy, P (1990)
Twenty patients with myotonic muscular dystrophy (MMD) were compared with twenty controls on a battery of standardised neuropsychiological tests measuring motor and cognitive functions. The MMD patients performed significantly poorer on both motor and cognitive tests, particularly those assessing spatial functions. Although both motor and cognitive scores were correlated with age, significant diagnostic group by age interactions were present only for the motor measures. Therefore, while motor deficits in MMD may progress with ageing, cognitive deficits are mainly developmental and relatively stable.